Pengaruh Good Corporate Govermance Terhadap Harga Saham (Studi Kasus Pada Perusahaan Food And Bevarage Di BEI Periode 2017-2021) - Septiana, Nani; Mazni, Afdal; Rahmawati, Ika (Universitas Muhammadiyah Metro, 2023)
Good Corporate Governance is the basis or guideline in conducting the company's internalmanagement. Stock prices are a reflection of the performance or value of the company andalso a reflection of investor confidence. The objectives to be achieved are: 1) To determine the effect of managerial ownership on stock prices in Food and Beverage companies on theIDX for the 2017-2021 period. 2) To determine the effect of institutional ownership on stockprices in Food and Beverage companies on the IDX for the 2017-2021 period. 3) Todetermine the effect of the size of the board of commissioners on the stock price of Food andBeverage companies on the IDX for the 2017-2021 period. 4) To determine the effect ofmanagerial ownership, institutional ownership and the board of commissioners on stockprices in Food and Beverage companies on the IDX for the 2017-2021 period. This researchis a quantitative research. The type of data used in this study is secondary data, namely GoodCorporate Governance on stock prices listed on the Indonesia Stock Exchange (IDX) in2017-2021. The data collection technique used in this research is documentation technique.The analytical technique used in this study is multiple regression analysis. The results ofresearch and data processing obtained the results of the t-test on the Managerial Ownershipvariable having a tcount of 5.444 where the tcount value is 5.444 > ttable 1.717, with asignificance value below 0.05, namely 0.000, then H1 is accepted. The results of the t-test ofthe institutional ownership variable have a tcount value greater than ttable or it can beexplained that the value (4.650 > 1.717) with a significance value below 0.05 is 0.000. Theresults of the t-test of the board of commissioners variable have a tcount value (5.502)greater than ttable (1.717) or it can be explained that the value of tcount > ttable (5.502 >1.717) with a significance value below 0.05, which is 0.000. The results of the F test on theindependent variables (managerial ownership, institutional ownership and the board ofcommissioners) have Fcount greater than Ftable or it can be explained that the value (18.776> 3.07) with a significance level below 0.05 is 0.000. Based on the results of the study, it canbe concluded that the test results simultaneously with the F test show that Good CorporateGovernance on indicators of managerial ownership, institutional election and independentcommissioners jointly affect stock prices in Food and Beverage companies listed on the IDXin 2017-2021. This is evidenced by statistical testing where tcount > ttable with asignificance less than 0.05. So it can be concluded that the results of this studysimultaneously (simultaneously) have a significant effect on stock prices.